THE EMERGING FUTURE OF AI CHATBOTS IN HIGHER EDUCATION - Sain, Zohaib Hassan; Vasudevan, Asokan; Lama, Alma Vorfi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2024)
Incorporating Artificial Intelligence (AI) chatbots within Higher Education Institutions (HEIs) is revolutionizing the educational domain, presenting new avenues for improved student support and administrative effectiveness. This research delves into the prospective impacts of AI chatbots in HEIs, focusing on their influence on teaching, learning, and research activities. Adopting a Narrative Literature Review (NLR) approach, the study compiles and synthesizes existing research on the role of AI chatbots in higher education, drawing from a wide range of academic sources and scholarly literature. The results underscore the significant potential of AI chatbots to streamline administrative functions, enrich student learning experiences, and facilitate research endeavours. Nonetheless, challenges such as concerns over academic integrity, difficulties in accurately interpreting user inputs, and the need for appropriate resource allocation present substantial barriers to the successful adoption of AI chatbots in HEIs. The study emphasizes the critical need for proactive strategies to address ethical issues, ensure comprehensive training for all stakeholders, and formulate clear guidelines for the responsible deployment of AI chatbots in higher education. By overcoming these challenges and capitalizing on the advantages of AI technologies, HEIs can fully exploit the capabilities of AI chatbots, thereby fostering a more efficient, effective, inclusive, and forward-thinking educational environment.